OBSTACLE DETECTION DEVICE - OHASHI, Akira; FAKUDA, Daisuke (2023)
An obstacle detecting device includes: an image converting portion for converting, into a circular cylindrical image, an image captured by a camera installed on a vehicle; a detection subject candidate image detecting portion for detecting a detection subject candidate image through pattern matching; an optical flow calculating portion for calculating an optical flow; an outlier removing portion for removing an optical flow that is not a detection subject; a TTC calculating portion for calculating a TTC (TTCX, TTCY); a tracking portion for generating a region of the detection subject on the circular cylindrical image by tracking the detection subject candidate; and a collision evaluating portion for evaluating whether or not there is the risk of a collision, wherein the optical flow calculating portion calculates the optical flow based on the detection subject candidate image and the region.